Novel carboxylated graphene oxide-CuS-Ag nanocomposite glass coating for organic degradation under solar light - Yu, Shuyan (2019)
BACKGROUD: Recently, semiconductor‐mediated heterogeneous photocatalysis has gained recognition as an effective treatment method for the removal of emerging organic contaminants (EOCs) from wastewater. The advantages of such technology include higher reaction rates for pollutant removal, complete mineralisation of the contaminants into harmless substances, e.g. water and carbon dioxide. Here, this study synthesized a hybrid multifunctional nanocomposite (GO‐COOH‐CuS‐Ag) via a facile method by integrating semiconductor copper sulfide (CuS) nanoflakes, carboxylic acid functionalised graphene oxide (GO‐COOH) sheets, and silver (Ag) nanoparticles, with the aim to enhance their EOCs photodegradation and antibacterial applications under solar light irradiation. RESULTS: The crystal phase, optical properties and morphology of the obtained composite were characterized using various characterization methods. The as‐synthesized GO‐COOH‐CuS‐Ag nanocomposites were transformed and applied on glass via a glass coating method aimed at facilitating their practical applications in photodegradation of emerging organic contaminants (EOCs) and disinfection for water treatment under solar light irradiation. The glass coatings had excellent photodegradation and antibacterial performance with good stability and repeatability. It was also found that synergistic reactions existed among CuS, Ag and GO‐COOH, and the mechanisms of charge transfer and photo‐disinfection were systematically investigated. CONCLUSION: The results clearly demonstrate its high performance potential in photodegradation and photo‐disinfection processes with the advantage of simplifying recovery and reuse in comparison with powdered forms, and reducing problems including the agglomeration of powdered particles that may cause blockages. © 2017 Society of Chemical Industry